2011
DOI: 10.1111/j.1365-2958.2011.07828.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of capsular polysaccharide at the division septum of Streptococcus pneumoniae is dependent on a bacterial tyrosine kinase

Abstract: SummaryOne of the main virulence factors of the pathogenic bacterium Streptococcus pneumoniae is the capsule, present at the bacterial surface, surrounding the entire cell. Virtually all the 90 different capsular serotypes of S. pneumoniae, which vary in their chemical composition, express two conserved proteins, Wzd and Wze, which regulate the rate of the synthesis of capsule. In this work, we show that Wzd, a membrane protein, and Wze, a cytoplasmic tyrosine kinase, localize at the bacterial division septum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 51 publications
10
54
1
Order By: Relevance
“…Indeed, we have shown that CpsD, as well as pneumococcal PTP CpsB, can act on LytA as a substrate in vitro, although as yet we have been unable to detect this in situ, probably due to low levels of LytA tyrosine phosphorylation. Previous studies illustrated that LytA as well as CpsD and BY-kinase adaptor protein CpsC locate to the septa of S. pneumoniae (De Las Rivas et al, 2002;Henriques et al, 2011;Mellroth et al, 2012), suggesting the possibility that these proteins co-localize, and further that there is a link between capsular polysaccharide synthesis and autolysis. Sun et al (2010) performed a phosphoproteomic study of the pneumococcus in which they showed that Y264 of LytA was phosphorylated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we have shown that CpsD, as well as pneumococcal PTP CpsB, can act on LytA as a substrate in vitro, although as yet we have been unable to detect this in situ, probably due to low levels of LytA tyrosine phosphorylation. Previous studies illustrated that LytA as well as CpsD and BY-kinase adaptor protein CpsC locate to the septa of S. pneumoniae (De Las Rivas et al, 2002;Henriques et al, 2011;Mellroth et al, 2012), suggesting the possibility that these proteins co-localize, and further that there is a link between capsular polysaccharide synthesis and autolysis. Sun et al (2010) performed a phosphoproteomic study of the pneumococcus in which they showed that Y264 of LytA was phosphorylated.…”
Section: Discussionmentioning
confidence: 99%
“…With CpsD the only BY-kinase identified to date in S. pneumoniae, and both proteins known to localize to the cell septum (Henriques et al, 2011;Mellroth et al, 2012), we hypothesized that CpsD plays a role in the phosphorylation of LytA, and that phosphorylation regulates its amidase activity. This study shows for the first time an effect of tyrosine phosphorylation on protein function in S. pneumoniae encoded outside of the capsule locus, and provides a hitherto unidentified link between cell autolysis and capsular polysaccharide biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we recently showed that a number of defined amino acid mutations in CpsC can affect capsule polymerisation, CpsD phosphorylation and ligation of capsule to the cell wall [84]. A recent study showed that while not affecting the attachment of capsule to the cell wall, CpsC and CpsD played critical roles in the synthesis of the capsule at the division septum [85]. This did not seem to require phosphorylation of CpsD, as the C-terminal cluster of tyrosines was not required.…”
Section: Regulationmentioning
confidence: 99%
“…A protein-protein interaction between the two homologous protein Wzd (CpsC homologue) and Wze (CpsD homologue) in S. pneumoniae has been shown previously (37). Having observed that CpsD autokinase activity required the presence of CpsC, we investigated a putative interaction between CpsC and CpsD of GBS using a bacterial two-hybrid system (28) (see "Experimental Procedures" for details).…”
Section: Analysis Of the Cps Operon Transcription In Cpsabcd Mutantmentioning
confidence: 99%
“…We created the mutant strains CpsC(⌬C-term) and CpsC(⌬ext), where the predicted intracellular tail (33 aa) and extracellular domain (101 aa) of CpsC were deleted. CpsD is potentially a kinase, by virtue of comparison with the orthologous proteins CapB in S. aureus (36) and Wzd in S. pneumoniae (37). The conserved catalytic residue Lys-49 was mutated into alanine, generating strain CpsD(K49A).…”
Section: Generation Of Isogenic Cpsabcd Mutant Strains In Gbs-mentioning
confidence: 99%